2013
DOI: 10.1186/1471-2229-13-181
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of the three homeologues of a new sucrose transporter in hexaploid wheat (Triticum aestivum L.)

Abstract: BackgroundSucrose transporters (SUTs) play important roles in regulating the translocation of assimilates from source to sink tissues. Identification and characterization of new SUTs in economically important crops such as wheat provide insights into their role in determining seed yield. To date, however, only one SUT of wheat has been reported and functionally characterized. The present study reports the isolation and characterization of a new SUT, designated as TaSUT2, and its homeologues (TaSUT2A, TaSUT2B a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 44 publications
(91 reference statements)
1
35
0
Order By: Relevance
“…Some of these clones have been shown to be functional SUTs by expressing them in Xenopus oocytes or yeast (Deol et al, 2013; Oner-Sieben et al, 2015; Zanon et al, 2015), but their ability to regulate plant metabolism remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these clones have been shown to be functional SUTs by expressing them in Xenopus oocytes or yeast (Deol et al, 2013; Oner-Sieben et al, 2015; Zanon et al, 2015), but their ability to regulate plant metabolism remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we investigated the molecular basis of the sucrose depletion metabolism in cereal crops. Previous studies in barley, wheat and rice demonstrated that the SUCROSE TRANSPORTER 2 (SUT2) is located in the vacuolar membrane and catalyzes the export of sucrose through a proton coupled co-transport (13, 14, 28, 29). Isolation of the sut2 -mutant in rice provided evidence in planta that SUT2 is necessary for the sucrose export from the vacuole into the cytoplasm as sut2 -mutant plants over-accumulated sucrose in the leaf vacuole at dawn (14).…”
Section: Resultsmentioning
confidence: 99%
“…This confirmed that the sucrose export from the leaf vacuole during the night affects growth and yield. The functional redundancy of the SUT2 transporter in rice, barley and wheat (13, 14, 28, 29) and the predominant consumption of sucrose instead of starch in these species during the night (Figure 5a) together with the growth reduction in cool nights (Figure 5b) suggests that the vacuolar sucrose exporter SUT2 is also a key regulator of the sucrose depletion metabolism and growth in barley and wheat. By contrast, Arabidopsis plants, which accumulate almost exclusively starch in the chloroplast during the day but almost no sucrose in the vacuole (Figure 1b), do not express the homologue of OsSUT2, AtSUT4/SUC4, in the leaf (30).…”
Section: Resultsmentioning
confidence: 99%
“…For example, StSUT1 of Solanum tuberosum, which is responsible for assimilation loading, also plays an important role in tuber phloem unloading (Kühn et al, 2003). SUT genes cloned from Galega officinalis (Li et al, 2011), Malus pumila (Peng et al, 2011), Triticum aestivum (Deol et al, 2013), and Leymus chinensis (Su et al, 2013) are expressed both in source leaves and sink tissues such as seeds, fruits, and stems. The present experiment revealed that PsSUT1 was critical to the allocation and utilization of sucrose in tree peony.…”
Section: Discussionmentioning
confidence: 99%